Kinetic analysis of different running starts: Impact on forward center of mass acceleration and performance - Termoz, N.; Lissajoux, K.; Slawinski, J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
In this study, three running starts allowing more or less large shifts of the centre of pressure (CoP) were compared in order to assess their impact on the forward acceleration of the centre of mass (CoM) and on the performance of a short distance run. Temporal and biomechanical parameters were calculated from CoP data in eighteen subjects. Our results suggested that an increase of the base of support by moving backward the CoP quickly after the start signal has a positive impact on the performance on short distance runs.